5. Modeling of Fouling from Molecular to Plant Scale5.2 Thermodynamic and Molecular Modeling - Jimenez,Serratos MG; Haslam,AJ; Jackson,G; Muller,EA (Gulf Professional Publishing, 2014)
With production from unconventional rigs continuing to escalate and refineries grappling with the challenges of shale and heavier oil feedstocks, petroleum engineers and refinery managers must ensure that equipment used with today’s crude ...